Innovation capability gaps in medium-sized enterprises of Chiriquí, Panamá: empirical evidence and strategic implications - Flores Franco, Alexis; Villarreal, Vladimir (Ingeniería Solidaria, 2025)
Introduction: This article is the result of the doctoral research project titled “Strategic Innovation Guidelines for Leveraging Organizational Resources in Medium-Sized Enterprises in the Province of Chiriquí,” carried out at the Universidad del Istmo during the 2024–2025 period. Problem: Previous studies suggest that weak competitive performance is linked to deficiencies in innovation capability (IC), particularly in its definition, management, and measurement. However, there is a lack of localized empirical evidence detailing these gaps. Objective: To diagnose the main limitations of IC in MEs in David–Chiriquí and propose strategic guidelines to transform available resources into sustainable competitive advantages. Methodology: A sequential exploratory mixed-methods design was employed. The qualitative phase involved 15 semi-structured interviews with business leaders; findings informed a 16-item Likert-scale survey applied to key employees (α = 0.87). The analysis used thematic coding and descriptive statistics. Main Results: Innovation is mainly reactive; none of the firms has a formal R&D unit. While 93.34% perceive efficient resource use, only 46.67% report consistently using updated technology. Although 86.67% allocate funds to innovation, knowledge remains largely tacit. These gaps limit both radical and incremental innovation. Implications: A four-phase roadmap is proposed—structured ideation, an internal innovation fund, knowledge management, and continuous improvement cells—to shift toward proactive innovation. Originality: This is the first post-pandemic diagnosis of IC in Panamanian MEs using a mixed-methods approach. Limitations: Non-probabilistic sampling and sectoral concentration restrict generalizability to other contexts.